Responding to Value Pluralism in Hybrid Organizations - Castellas, Erin I. (Journal of business ethics, 2019)
In this paper, we derive a four-stage process model of how hybrid organizations respond to specific challenges that arise under conditions of value pluralism and institutional complexity. Engaging in exploratory qualitative research of six Australian hybrid organizations, we identify institutional and organizational responses to pluralism, particularly as organizations strive to uphold multiple value commitments, such as social, environmental and/or financial outcomes. We find that by employing a process of separating, negotiating, aggregating, and subjectively assessing the value that is created, our cases demonstrate how they move between logics in a dynamic fashion and address specific challenges of cognitive dissonance, incommensurability, interdependence and aggregation. Our model contributes to the literature by reframing the notion of ‘tensions’ that arise in conditions of hybridity and characterize specific challenges and sequential responses that may go some way to addressing why some hybrids employ particular responses to pluralism and why some succeed.